345. Italian diagnostic reference levels for diagnostic and interventional radiology. (December 2018) - Padovani, R.; Compagnone, G.; D'Ercole, L.; Orlacchio, A.; Bernardi, G.; Rosi, A.; Campanella, F.
Abstract : Purpose: The Diagnostic reference level (DRL) is recognised as an important tool in identifying high and non-justified exposure levels in diagnostic imaging practice and, in general, in the optimisation practice of patient exposure. In Italy, the D.Lgs. 187/2000 has introduced a set of DRL values and has requested their use in the medical exposure practice. Since many years, it has recognised this set, derived from European guidelines published in the 90', requires an update to assure the efficacy of the tool. Methods: In the last decade, with this in mind professional societies and national institutes have developed national surveys to assess level of patient exposure in different areas of diagnostic imaging. These data, together with relevant European data, have supported the development of the ISS ISTISAN 17/33 publication aiming to propose to the radiology community an updated set of national DRL values for the diagnostic and interventional radiology, i.e. general radiography, fluoroscopy and CT for adult and paediatric patients and interventional radiology for adults[1] . Results and Conclusions: The ISS document can serves as a reference in the forthcoming legislative decree implementing the Council Directive 2013/59/EURATOM of 5/12/2013, laying down basic safety standards for protection against the dangers arising from exposure to ionising radiation, has been transposing at national level. Because the Directive identifies in the DRLs a useful tool to support the optimisation also in interventional radiology (IR), a practice rapidly increasing and representing a critical scenario from the point of patient radiation protection, the ISS document is introducing DRLs for the most common IR procedures.